The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/anie.201206971
|View full text |Cite
|
Sign up to set email alerts
|

Silver‐Catalyzed Allenylation and Enantioselective Propargylation Reactions of Ketones

Abstract: More than a silver lining: Certain silver complexes are capable of selective catalysis of either allenylation or asymmetric propargylation reactions of ketones. Ligand‐free conditions lead to allenyl alcohols as the major product, whereas ligation with Walphos‐8 gives enantioenriched homopropargyl alcohols. This method can be applied to reactions of prochiral diarylketones to provide optically enriched tertiary diaryl alcohols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 53 publications
(35 reference statements)
0
17
0
Order By: Relevance
“…Under the latter conditions, site selectivities improved (e.g., 97% vs 91% S N 2′ for 10b vs 9b) and the er values remained nearly the same (entries 5 and 7, Table 1). With the NHC−Cu catalyst generated from dimeric Ag complex 10c, the desired product was formed in lower and, notably, with a preference for the alternative product 21 The initial screening revealed an unusual selectivity pattern. Unlike the products derived from propargyl addition, where the branched isomer (3a) is formed in preference to the linear product (5a), when an allenyl unit is introduced, it is only the achiral linear adduct (6a) that is generated (i.e., <2% 4a by analysis of 1 H NMR spectra of the unpurified mixtures).…”
Section: ■ Introduction and Backgroundmentioning
confidence: 99%
“…Under the latter conditions, site selectivities improved (e.g., 97% vs 91% S N 2′ for 10b vs 9b) and the er values remained nearly the same (entries 5 and 7, Table 1). With the NHC−Cu catalyst generated from dimeric Ag complex 10c, the desired product was formed in lower and, notably, with a preference for the alternative product 21 The initial screening revealed an unusual selectivity pattern. Unlike the products derived from propargyl addition, where the branched isomer (3a) is formed in preference to the linear product (5a), when an allenyl unit is introduced, it is only the achiral linear adduct (6a) that is generated (i.e., <2% 4a by analysis of 1 H NMR spectra of the unpurified mixtures).…”
Section: ■ Introduction and Backgroundmentioning
confidence: 99%
“…Silver salts are also known to catalyze propargylation of ketones only with the aid of ligands for site selection. [7a] However, an isatin derivative screen of silver metal sources revealed that propargylation occurred with high regioselectivity in each case (Table , Entries 9, 10 and 11), albeit in poor yield with silver nitrate salt (Table , Entry 11). This behavior of silver and copper showed that the counterions are assisting in the reactivity and nature of metal in the regioselectivity.…”
Section: Resultsmentioning
confidence: 99%
“…The advancements made so far in the development of the new methodology for functionalized tertiary alcohols use a stoichiometric amount of propargyl metal species. [1c], However, recent trends in this area of organic transformations have used allenylboronic acid pinacol ester as the starting material for regioselective propargylation and allenylation by using organocatalysts[5b], [5e], and different metals, such as Ag, Zn, and Cu as Lewis acids . However, the site selection for the formation of propargyl and allenyl substitutes remain a challenging task because of the formation of stable allenyl and less stable propargyl intermediates .…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other types of ketones, the catalytic enantioselective propargylation of diaryl ketones was much more difficult due to the smaller size difference between the two aryl groups. Jarvo and co‐workers made a breakthrough on this challenge reaction . They recently discovered that a variety of diaryl‐substituted homopropargyl tertiary alcohols 55 could be formed with up to 95% yield and 97% ee value when 5 mol% of AgF, 5 mol% of ( R , R )‐Walphos 54 and 30 mol% of t‐ BuONa were applied (Scheme ).…”
Section: Catalytic Asymmetric Nucleophilic Addition Of Organometallicmentioning
confidence: 99%